The Effect of Customer Relationship Management on Marketing Performance Mediated by Competitive Advantage and Innovation (Study on Area Managers of Pharmaceutical Companies in East Java during the COVID-19 Pandemic) - Musonnafa, Moh Alim; Sumiati, Prof; Djazuli, Dr Atim (AIBPM Publisher, 2022)
The pharmaceutical industry is one of the industries that has experienced significant development in Indonesia. The growth of this sector can be seen in the increasing total market share from year to year. However, the pharmaceutical industry faces several challenges such as the high level of competition and a dynamic business situation. One of them is the COVID-19 pandemic which also affects the condition of the pharmaceutical industry in Indonesia. This study aims to examine and analyze the role of CRM on the marketing performance of the pharmaceutical industry through the mediation of competitive advantage and innovation. A total of 151 respondents were involved in this study and the data were processed through PLS analysis. The results find that CRM has a significant effect directly on Competitive Advantage and Innovation. While CRM is not proven to have a significant effect directly on Marketing Performance. However, CRM has a significant effect indirectly through the mediation of Competitive Advantage and Innovation.